The Effect of Tourism Products and Facilities on The Revisit of Tourist Intention to Curug Cimahi - Rahmat Priyanto; Ricky Pemala (Media Wisata, 2023)
This study aims to analyze the effect of tourism products and facilities on the revisit intention of tourists to Curug Cimahi. This research uses a descriptive verification method. The sample of this research is one hundred respondents who have visited Curug Cimahi at least once between 2019 and 2022. Primary data were obtained through interviews, observations, and questionnaires, while secondary data sources were obtained through a literature review. The results show that partially tourism products and facilities affect the revisit intention of tourists to Curug Cimahi, while simultaneously, tourism products and facilities affect the revisit intention of tourists to Curug Cimahi. This can be an input for managers of Curug Cimahi tourist destinations to develop tourism objects in the future.